2020
DOI: 10.1021/acs.langmuir.0c03261
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking Biosintering: The Identification of Highly Condensed Surfaces in Bioinspired Silica Materials

Abstract: Interfacial interactions between inorganic surfaces and organic additives are vital to develop new complex nanomaterials. Learning from biosilica materials, composite nanostructures have been developed, which exploit the strength and directionality of specific polyamine additive-silica surface interactions. Previous interpretations of these interactions are almost universally based on interfacial charge matching and/or hydrogen bonding. In this study, we analyzed the surface chemistry of bioinspired silica (BI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Polyamine-embedded silicas have been used as catalysts and in water remidiation 63 . Furthermore, by posttreatment polyamine-incorporated silicas can be further processed to improve hydrothermal stability of silica 64 . Recently 65 , it has been demonstrated that through the use of cyclams and methylated diamines silica particles can be assembled to produce tuneable hollow structures.…”
Section: Discussionmentioning
confidence: 99%
“…Polyamine-embedded silicas have been used as catalysts and in water remidiation 63 . Furthermore, by posttreatment polyamine-incorporated silicas can be further processed to improve hydrothermal stability of silica 64 . Recently 65 , it has been demonstrated that through the use of cyclams and methylated diamines silica particles can be assembled to produce tuneable hollow structures.…”
Section: Discussionmentioning
confidence: 99%
“… 44 In earlier work, an unproven multistep nonclassical formation pathway was postulated (see Figure 3 b). In terms of understanding the BIS reaction pathways and, more specifically, elucidating the molecular-scale mechanisms that underpin synthesis–property relationships, two avenues of inquiry have been pursued recently: a sequential DoE strategy for systematic and quantitative investigation of the BIS system’s reaction space and 16 a combination of experimental measurements (advanced characterization, including solid state NMR 45 ) and computation (multiscale modeling, including molecular dynamics simulations 46 ) to investigate the additive-silica interface at molecular length-scales. …”
Section: Pathway Understandingmentioning
confidence: 99%
“…a combination of experimental measurements (advanced characterization, including solid state NMR 45 ) and computation (multiscale modeling, including molecular dynamics simulations 46 ) to investigate the additive-silica interface at molecular length-scales.…”
Section: Pathway Understandingmentioning
confidence: 99%
See 2 more Smart Citations